Multilayer adhesive article and method

By employing a multi-layered bonding tape, curable adhesive compositions using thermoplastic polymers and epoxy resins and polyvinyl acetal polymers, high curing at room temperature and under ultraviolet irradiation is achieved. The modulus strip material solves the problem that the strip material is difficult to resist impact forces simultaneously in the tensile and shear directions in the prior art.

CN119421783APending Publication Date: 2025-02-113M INNOVATIVE PROPERTIES CO
View PDF 24 Cites 0 Cited by

Patent Information

Application Number
CN202380049766.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-29
Filing Date
2023-06-07
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing electronic display bonding tapes are difficult to resist impact forces simultaneously in the tensile and shear directions, and high pressure and high temperature are required to form a waterproof seal during the assembly process of mobile phones.

Method used

Using a multilayer structure including a first layer of curable adhesive composition and a second layer of polyvinyl acetal polymer, the first layer consisting of a thermoplastic polymer and an epoxy resin, capable of being soft at room temperature and irradiated with ultraviolet light. and cure under the curing to form a strip with impact resistance, dynamic shear resistance and push-out resistance.

Benefits of technology

It realizes waterproof sealing at room temperature and forms a strip with high modulus and impact resistance under ultraviolet irradiation, solving the problem that the strip is difficult to resist impact forces at the same time in the tensile and shear directions in the prior art. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119421783A_ABST
    Figure CN119421783A_ABST
Patent Text Reader

Abstract

An article is described that includes a first layer disposed on a second layer, the first layer including a curable adhesive composition, and the second layer including a polyvinyl acetal polymer. The curable adhesive composition comprises a thermoplastic polymer, such as an acrylic block copolymer; an epoxy resin; and a preferred polyol. Methods and curable adhesive compositions are also described.
Need to check novelty before this filing date? Find Prior Art

Description

DETAILED DESCRIPTION

[0001] In the consumer electronics industry, there is a need for electronic display bonding materials. For example, in mobile phone display bonding, there is a need for tapes that can resist both drops and impacts. Some electronic device original equipment manufacturers ("OEMs") use tensile impact test methods to evaluate the drop resistance of tape candidates, while other OEMs prioritize dynamic shear test methods. In an actual phone device drop, there are both tensile and shear forces, so it is very important that the display bonding tape can resist impact forces in both the tensile and shear directions.

[0002] Another important tape property is push-out resistance, which can be tested by debonding two rigid substrates in a slow-stretch direction. Stiff, high-modulus tapes typically exhibit properties such as dynamic shear resistance and push-out resistance. Unfortunately, during the cell phone assembly process, stiff, high-modulus tapes typically require high pressure and temperature to form a watertight seal between two rigid substrates. BRIEF DESCRIPTION OF THE DRAWINGS

[0003] Figure 1 is a schematic diagram of an extrusion process suitable for preparing a multi-layer adhesive article. Summary of the invention

[0004] In one embodiment, an article is described that includes a first layer that includes a curable adhesive composition. The curable adhesive composition includes a thermoplastic polymer and an epoxy resin.

[0005] The first layer is disposed on a second (e.g., backing or carrier) layer comprising a polyvinyl acetal polymer. Without being bound by theory, it is speculated that the hydroxyl groups of the polyvinyl acetal polymer react with the epoxy groups of the epoxy resin to provide good interlayer adhesion between the adhesive of the first layer and the second (e.g., backing or carrier) layer. In some embodiments, the thermoplastic polymer comprises an acrylic block copolymer.

[0006] In one advantageous embodiment, the adhesive composition comprises 20 to 60 weight percent of an acrylic block copolymer; 5 to 60 weight percent of an epoxy resin; and 1 to 60 weight percent of a polyol.

[0007] The (e.g., tape) article is initially soft (i.e., low modulus), which enables a watertight seal to be achieved during assembly at room temperature, and can then be UV cured into a rigid (i.e., high modulus) tape having a balance of impact resistance (tensile and shear impact), dynamic shear resistance, and push-out resistance.

[0008] In another embodiment, a method of making an adhesive article is described, the method comprising: thermally extruding a first layer and a second layer, as described herein.

[0009] Thermoplastic polymers

[0010] The curable adhesive comprises a thermoplastic polymer. The thermoplastic polymer can be changed from a solid to a liquid using heat rather than a solvent. Therefore, the curable adhesive composition can advantageously be substantially free of solvent (i.e., less than 1 wt%, 0.5 wt%, or 0.1 wt% of an organic solvent).

[0011] In a typical embodiment, the thermoplastic polymer is one or more block copolymers comprising at least two A block polymer units and at least one B block polymer unit (i.e., at least two A block polymer units are each covalently bonded to at least one B block polymer unit). Each A block is derived from a first (meth) acrylate monomer, and the B block is derived from a second (meth) acrylate monomer. The A block tends to be more rigid than the B block (i.e., the A block has a higher glass transition temperature than the B block). The A block is also referred to herein as a "hard block" and the B block is also referred to herein as a "soft block". The difference between acrylic block copolymers and other acrylic copolymers is that they exhibit phase separation at temperatures below the glass transition temperature of the end blocks. This results in elastomeric properties below this temperature and the ability to be solvent-free compounded above this temperature. The result of this behavior may be that materials compounded with acrylic block copolymers have excellent rolling stability and static shear properties compared to random acrylic copolymer counterparts. In some embodiments,

[0012] The (eg acrylic) block copolymers include ABA triblock copolymers.

[0013] In some embodiments, the (e.g., acrylic) block copolymer comprises at least 7%, 8%, 9%, or 10% by weight and no more than 51% by weight of hard blocks ("A blocks") and 49% to 93% by weight of soft blocks ("B blocks"), based on the weight of the block copolymer. In some embodiments, the (e.g., acrylic) block copolymer comprises at least 15% or 20% by weight of hard blocks. In some embodiments, the (e.g., acrylic) block copolymer comprises no more than 45%, 40%, or 25% by weight of hard blocks. Higher amounts of A blocks tend to increase the hardness or modulus of the copolymer, which can be used to optimize the properties of the composition, such as mechanical strength and modulus.

[0014] In some preferred embodiments, one or both of the blocks are non-reactive during the UV-activated epoxy reaction (e.g., one or both blocks do not contain pendant epoxy functional groups or hydroxyl functional groups). In some preferred embodiments, the hard block comprises polymethyl methacrylate. In some preferred embodiments, the soft block comprises polybutyl acrylate. Methods for preparing acrylic block copolymers are known to those skilled in the art and are described in, for example, U.S. Patent No. 6,806,320 (Everaerts et al.). Acrylic block copolymers useful in embodiments of the present disclosure are also commercially available, for example, under the trade name "KURARITY" from Kuraray CO., Tokyo, Japan.

[0015] In some embodiments, (e.g., acrylic acid) block copolymers have a weight average molecular weight of at least 30 g / mol, 40 g / mol, or 50,000 g / mol, as measured by gel permeation chromatography using the test method described in the examples. (e.g., acrylic acid) block copolymers typically have a weight average molecular weight of no more than 200,000 g / mol, 175,000 g / mol, 150,000 g / mol, 125,000 g / mol, or 100,000 g / mol. In some embodiments, (e.g., acrylic acid) block copolymers have a weight average molecular weight of at least 60,000 g / mol, 70,000 g / mol, 80,000 g / mol, 90,000 g / mol, or 100,000 g / mol. In some embodiments, the (e.g. acrylic) block copolymer has a weight average molecular weight of no greater than 100,000 g / mol, 90,000 g / mol, 80,000 g / mol, 70,000 g / mol, or 60,000 g / mol. In some embodiments, the (e.g. acrylic) block copolymer has a number average molecular weight greater than 102 kD or 110 kD (i.e., 102,000 g / mol or 110,000 g / mol). The curable adhesive composition may comprise a single (e.g. acrylic) block copolymer or a blend of higher and lower molecular weight copolymers.

[0016] Melt flow rate (MFR) is another way to express molecular weight (as determined using ISO 1133). In some embodiments, the (e.g. acrylic) block copolymer has an MFR of at least 2 g / 10 min, 3 g / 10 min, or 4 g / 10 min at a temperature of 190° C. and a weight of 2.16 kg. In some embodiments, the (e.g. acrylic) block copolymer has an MFR of no more than 60 g / 10 min, 50 g / 10 min, 40 g / 10 min, or 30 g / 10 min at a temperature of 190° C. and a weight of 2.16 kg. In some embodiments, the MFR of the (e.g. acrylic) block copolymer is at least 5 g / 10 min, 10 g / 10 min, 15 g / 10 min, 20 g / 10 min, 25 g / 10 min, or 30 g / 10 min at a temperature of 190° C. and a weight of 2.16 kg. In some embodiments, the (eg acrylic) block copolymer has an MFR of less than 30, 25, 20, 15, 10, or 5 g / 10 min at a temperature of 190°C and a weight of 2.16 kg.

[0017] In some embodiments, based on the total weight of thermoplastic block copolymer, epoxy resin and polyol, the curable adhesive composition comprises at least 20 wt %, 25 wt %, 30 wt %, 35 wt % or 40 wt % of thermoplastic block copolymer. The amount of thermoplastic polymer is usually not more than 60 wt %, 55 wt % or 50 wt %.

[0018] Epoxy resin

[0019] Based on the total amount of thermoplastic block copolymer, epoxy resin and polyol, curable adhesive composition comprises at least 5 % by weight, 10 % by weight, 15 % by weight or 20 % by weight and is not more than 60 % by weight, 55 % by weight, 50 % by weight or 45 % by weight of epoxy resin.Multiple commercially available epoxy resins can be used in curable compositions of the present disclosure.Usually, available epoxy resins can have an epoxide equivalent weight of 150 to 250.

[0020] In some embodiments, the epoxy resin may include a first epoxy resin and a second epoxy resin combined in a ratio of 0.5:1.5, optionally 0.75:1.25, or optionally 1: 1. In some embodiments, the second epoxy resin has an epoxy equivalent weight of about 500 to about 600.

[0021] In some preferred embodiments, the epoxy resin comprises an epoxy resin derived from bisphenol A. Examples of such preferred epoxy resins include, but are not limited to, a difunctional bisphenol A / epichlorohydrin derived epoxy resin commercially available from Dow Inc., Midland, Michigan, under the trade name "EPON 828" and a difunctional bisphenol A / epichlorohydrin derived epoxy resin commercially available from Dow Inc., Midland, Michigan, under the trade name "EPON 1001F".

[0022] Polyols

[0023] Curable adhesive composition as herein described comprises polyol.Term polyol refers to have at least two hydroxyl groups and molecular weight is at least 500g / mol, 1000g / mol, 1500g / mol or 2000g / mol and is not more than 14,000g / mol material.Based on the total amount of thermoplastic block copolymer, epoxy resin and polyol, curable adhesive composition generally comprises at least 1 % by weight, 2 % by weight, 3 % by weight, 4 % by weight or 5 % by weight and is not more than 60 % by weight, 55 % by weight or 50 % by weight polyol.In some embodiments, the amount of polyol is at least 6 % by weight, 7 % by weight, 8 % by weight, 9 % by weight, 10 % by weight, 11 % by weight, 12 % by weight, 13 % by weight, 14 % by weight or 15 % by weight polyol.

[0024] When using higher molecular weight polyols (i.e., polyols having a weight average molecular weight of at least about 2,000), it is generally desirable that the polyol component be "high purity" (i.e., the polyol is close to its theoretical functionality, e.g., 2.0 for diols, 3.0 for triols, etc.). Such high purity polyols generally have a ratio of polyol molecular weight to weight percent hydroxyl equivalents of at least about 800, typically at least about 1,000, and more typically at least about 1,500. For example, a 12,000 molecular weight polyol having 8 weight percent hydroxyl equivalents has such a ratio of 1,500 (i.e., 12,000 / 8=1,500).

[0025] Examples of high purity polyols useful in embodiments of the present disclosure include those available under the trade designation ACCLAIM from Covestro AG, Luverkusen, Germany, and certain polyols available under the trade designation ARCOL.

[0026] Curing agent

[0027] The curable composition optionally but usually also contains one or more curing agents. The term "curing agent" is used in a broad sense, including not only those materials that are traditionally considered to be curing agents, but also those materials that catalyze or accelerate the reaction of the curable material, and those materials that can act as both a curing agent and a catalyst or accelerator. Two or more curing agents can also be used in combination. The curing agent can be a heat-activated curing agent or a light-activated curing agent. The curing from the light-activated curing agent can be optionally accelerated by an elevated temperature (e.g., 40° C.-80° C.).

[0028] In some embodiments, the adhesive comprises a first photoacid curing agent (e.g., O432 and CPI6976) that absorbs light and then produces acid. The acid catalyzes the polymerization of epoxy groups and polyols. Exposure to light generally occurs after the adhesive is applied to concrete or a road surface. Alternatively, the epoxy curing agent may also be incorporated into a primer applied to the surface. The adhesive is then adhered to the surface coated with the primer. In this embodiment, the adhesive may not contain a curing agent. The epoxy groups react with the polyols at a slow rate in the absence of a curing agent.

[0029] Suitable curing agents for use in embodiments of the present disclosure include, but are not limited to, those disclosed in U.S. Pat. Nos. 4,503,211 (Robins), 4,751,138 (Tumey et al.), and 10,774,245 (Emslander et al.), the disclosures of all of which are incorporated by reference in their entirety.

[0030] In the reactive polyacrylate / epoxy hybrid system having reactive functional groups, the amount of photoinitiator used in the UV-curable pressure-sensitive adhesive composition is very small, but its amount has a great influence on the curing speed and storage stability of the UV-curable pressure-sensitive adhesive composition.

[0031] The photoinitiator can be a cationic photoinitiator, including but not limited to onium salts and cationic organometallic salts (both of which are described in U.S. Pat. No. 5,709,948) and photoactivatable organometallic complex salts (such as those described in U.S. Pat. Nos. 5,059,701, 5,191,101 and 5,252,694). Suitable cationic photoinitiators include but are not limited to the following compounds: diaryl iodonium salts, triaryl sulfonium salts, alkyl sulfonium salts, iron arene salts, sulfonyloxanone and triaryl siloxanes. In some embodiments, the following compounds are used: triaryl sulfonium hexafluorophosphate or hexafluoroantimonate, sulfonium hexafluoroantimonate, sulfonium hexafluorophosphate and iodonium hexafluorophosphate.

[0032] Onium salt photoinitiators suitable for use in the present invention include, but are not limited to, iodonium and sulfonium complex salts. Suitable aromatic iodonium complex salts are more fully described in U.S. Pat. No. 4,256,828. Useful aromatic iodonium complex salts include salts of the general formula:

[0033]

[0034] Ar 1 and Ar 2 are the same or different, each comprising an aromatic group having about 4 to 20 carbon atoms. Z is selected from the group consisting of oxygen, sulfur, and a carbon-carbon bond;

[0035]

[0036] R may be an aryl group (having about 6 to 20 carbon atoms, such as a phenyl group) or an acyl group (having about 2 to 20 carbon atoms, such as an acetyl group or a benzoyl group); and

[0037]

[0038] R 1 and R 2 Selected from the group consisting of hydrogen, an alkyl group having about 1 to 4 carbon atoms, and an alkenyl group having about 2 to 4 carbon atoms.

[0039] m is 0 or 1; and

[0040] X has a chemical formula of DQn, wherein D is a metal of Groups IB to VIII or a nonmetal of Groups IIIA to VA of the Periodic Table, or a combination thereof, and D further includes hydrogen; Q is a halogen atom; and n is an integer from 1 to 6. The metal is preferably copper, zinc, titanium, vanadium, chromium, magnesium, manganese, iron, cobalt or nickel, and the nonmetal is advantageously boron, aluminum, antimony, tin, arsenic and phosphorus. The halogen Q is preferably chlorine or fluorine. Suitable examples of anions include, but are not limited to, BF 4 - PF 6 - , SbF 6 - 、FeCl 4 - SnCl 5 - , AsF 6 - , SbF 5 OH - 、SbCl 6 - , SbF 5 -2 , AlF 5 -2 、GaCl 4- 、InF 4 - 、TiF 6 -2 , ZrF 6 - and CF 3 SO 3 - The anion is preferably BF 4 - PF 6 - , SbF 6 - , AsF 6 - , SbF 5 OH - and SbCl 6 - More preferably, the anion is SbF 6 - , AsF 6 - and SbF 5 OH - .

[0041] More preferably, Ar 1 and Ar 2 is selected from the group consisting of a phenyl group, a thienyl group, a furyl group and a pyrazolyl group. 1 and Ar 2 The group may optionally contain one or more condensed benzene rings (e.g., naphthyl, benzothienyl, dibenzothienyl, benzofuranyl, and dibenzofuranyl). If the aryl group is substantially inert to epoxy compounds and hydroxyl functional groups, the aryl group also needs to be substituted with one or more non-basic groups.

[0042] The aromatic sulfonium complex salt initiator suitable for use in the present invention can be represented by the following general formula:

[0043]

[0044] Where R 3 , R 4 and R 5 Same or different, provided that R 3 , R 4 and R 5 At least one of R is an aryl group. 3 , R 4 and R 5 It may be selected from the group consisting of an aromatic moiety containing about 4 to 20 carbon atoms (e.g., substituted and unsubstituted phenyl, thienyl, and furyl) and an alkyl group containing about 1 to 20 carbon atoms.3 , R 4 and R 5 Each is preferably an aromatic moiety; and Z, m and X are all those defined for the above-mentioned sulfonium complex salts.

[0045] If R 3 , R 4 and R 5 If the aryl groups are aromatic, they may optionally contain one or more condensed benzene rings (e.g., naphthyl, benzothienyl, dibenzothienyl, benzofuranyl and dibenzofuranyl). If the aryl groups are substantially inert to epoxy compounds and hydroxyl functional groups, the aryl groups also need to be substituted with one or more non-basic groups.

[0046] In one example of the present invention, triaryl substituted salts such as triphenylsulfonium hexafluoroantimonate, triphenylsulfonium hexafluorophosphate, and p-phenyl(phenylthio)biphenylsulfonium hexafluoroantimonate are preferred sulfonium salts. Other sulfonium salts useful in the present invention are more fully described in U.S. Pat. Nos. 4,256,828 and 4,173,476.

[0047] Onium salt photoinitiators useful in the present invention are photosensitive in the ultraviolet region of the spectrum. However, they can be sensitized to the near ultraviolet and visible spectral ranges by known sensitizers of photolyzable organic halogen compounds. Exemplary sensitizers include colored aromatic polycyclic hydrocarbons as described in U.S. Pat. No. 4,250,053 and sensitizers as described in U.S. Pat. Nos. 4,256,828 and 4,250,053. Suitable sensitizers should be selected so as not to significantly interfere with the cationic cure of the epoxy resin in the adhesive composition.

[0048] Another type of photoinitiator suitable for use in the present invention includes photoactivatable organometallic complex salts such as those described in U.S. Pat. Nos. 5,059,701 (Keipert), 5,191,101 (Palazzotto et al.), and 5,252,694 (Willett et al.). These organometallic cation salts have the following general formula:

[0049] [(L 1 )(L 2 )M m ]e + X -

[0050] Among them, M m represents an element selected from Groups IVB, VB, VIB, VIIB and VIII of the Periodic Table, and is preferably Cr, Mo, W, Mn, Re, Fe or Co; L 1represents no ligand or represents 1 or 2 ligands that donate π electrons, wherein the ligands may be the same or different, and each ligand may be selected from the group consisting of substituted and unsubstituted alicyclic and cyclic unsaturated compounds, substituted and unsubstituted carbocyclic aromatic and heterocyclic aromatic compounds. Each of the compounds may donate 2 to 12 π electrons to the valence electron shell of the metal atom M. L 1 Advantageously selected from the group consisting of substituted and unsubstituted η3-allyl, η5-cyclopentadienyl and η7-cycloheptane compounds and η6-aromatic compounds (e.g., xylene) from η6-benzene and substituted η6-benzene compounds and compounds having 2-4 fused rings, each ring being capable of donating 3 to 8 π electrons to the valence electron shell of the metal atom M.

[0051] L 2 represents no ligand or represents one to three ligands that contribute an even number of σ electrons, wherein the ligands may be the same or different and are represented by L 1 and L 2 To M m Each ligand may be selected from the group consisting of carbon monoxide, onium nitrite, triphenylphosphine, triphenylantimony and phosphorus, arsenic and antimony derivatives under conditions where the total charge contributed results in a net residual positive charge e of the complex.

[0052] e is an integer of 1 or 2, the remaining charge coordinated to the cation; and X is a coordinated halogen-containing anion, as described above.

[0053] Examples of organometallic complex cation salts suitable for use as photoactivatable catalysts in the present invention include, but are not limited to, the following:

[0054] [(η6-phenyl)(η5-cyclopentadienyl)Fe] + [SbF 6 ] - ,

[0055] [(η6-Toluene)(η5-cyclopentadienyl)Fe] + [AsF 6 ] - ,

[0056] [(η6-Dimethylbenzene)(η5-cyclopentadienyl)Fe] + [SbF 6 ] - ,

[0057] [(η6-Isopropylbenzene)(η5-cyclopentadienyl)Fe] + [SbF 6 ] - ,

[0058] [(η6-xylene (mixed isomers))(η5-cyclopentadienyl)Fe] + [SbF 6 ] - ,

[0059] [(η6-xylene (mixed isomers))(η5-cyclopentadienyl)Fe] + [PF 6 ] - ,

[0060] [(η6-o-xylene)(η5-cyclopentadienyl)Fe] + [CF 3 SO 3 ] - ,

[0061] [(η6-m-xylene)(η5-cyclopentadienyl)Fe] + [BF 4 ] - ,

[0062] [(η6-1,3,5-Trimethylbenzene)(η5-cyclopentadienyl)Fe] + [SbF 6 ] - ,

[0063] [(η6-Hexamethylbenzene)(η5-cyclopentadienyl)Fe] + [SbF 5 OH] - ,

[0064] [(η6-fluorene)(η5-cyclopentadienyl)Fe] + [SbF 6 ] - .

[0065] In one example of the present invention, the desired organometallic complex cation salt includes one or more of the following compounds:

[0066] [(η6-xylene (mixed isomers))(η5-cyclopentadienyl)Fe] + [SbF 6 ] - ,

[0067] [(η6-xylene (mixed isomers))(η5-cyclopentadienyl)Fe] + [PF 6 ] - ,

[0068] [(η6-Dimethylbenzene)(η5-cyclopentadienyl)Fe] + [SbF 6] - ,

[0069] [(η6-1,3,5-Trimethylbenzene)(η5-cyclopentadienyl)Fe] + [SbF 6 ] - ,

[0070] Suitable commercially available initiators include, but are not limited to, DOUBLECURE 1176, 1193 (Double Bond Chemical Ind. Co., Ltd.) and IRGACURE™ 261, and cationic organometallic complex salts (BASF). Photoinitiators include, but are not limited to, azo initiators and peroxide initiators, such as azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), 2,2'-azo-bis(2-methylbutyronitrile) (AMBN), benzoyl peroxide (BPO), and persulfates.

[0071] In the composition of the present invention, the content of the photoinitiator is 0.05 to 5 parts by weight, preferably 1 to 2 parts by weight. In general, the curing speed of the adhesive composition increases due to the increase in the content of the photoinitiator. When the amount of the photoinitiator used is too low, the ultraviolet radiation energy required during curing is high, and the curing speed is slow. On the contrary, when the amount of the photoinitiator used is too large, the ultraviolet radiation energy required during curing is very low, and the curing speed is too fast. Even under sunlight or fluorescent light (containing a small amount of ultraviolet light), the photoinitiator can be cured, thereby affecting the storage stability at room temperature.

[0072] The curable composition of the present disclosure generally comprises 0.5 wt % to 10 wt %, optionally 0.75 wt % to 8 wt %, or optionally 1 wt % to 0.5 wt % of a curing agent. Typically, the curing agent is selected from the group consisting of an amine curing agent, a photoinitiator, and a combination thereof.

[0073] Optional additives

[0074] The curable composition may also optionally contain one or more additives, such as, for example, an additive selected from the group consisting of microspheres, styrene block copolymers, epoxidized natural rubber, and combinations thereof. In some preferred embodiments, the curable composition comprises up to 5% by weight of microspheres, such as expandable polymer microspheres obtainable from Chase Corp., Westwood, MA, USA under the trade name DUALITE. In some preferred embodiments, the curable composition comprises 10% by weight of styrene block copolymers. In some preferred embodiments, the curable composition comprises up to 60% by weight of epoxidized natural rubber.

[0075] The curable composition may also contain one or more additional conventional additives. Preferred additives may include, for example, tackifiers, plasticizers, dyes, antioxidants, UV stabilizers, and combinations thereof. If such additives do not affect the excellent properties of the pressure-sensitive adhesive, such additives may be used.

[0076] If a tackifier is used, then based on the dry weight of the curable composition, up to 50 wt %, preferably less than 30 wt % and more preferably less than 5 wt % will be suitable. In some embodiments, no tackifier is used. Suitable tackifiers for use with the (meth)acrylate polymer dispersion include rosin acids, rosin esters, terpene phenolic resins, hydrocarbon resins and coumarone indene resins. The type and amount of the tackifier can affect properties such as contactability, bonding range, bond strength, heat resistance and specific adhesion.

[0077] Curable compositions as disclosed herein can be prepared by methods known to those skilled in the relevant art or those of ordinary skill. For example, curable compositions can be prepared by combining copolymers with epoxy resins, polyols, curing agents and optionally coating the mixture. In some embodiments, the combination step includes melt blending. In some embodiments, the combination step includes solvent blending.

[0078] Physical properties of adhesive or product

[0079] Various test methods can be utilized to characterize the physical properties of adhesive compositions and articles.

[0080] Uncured adhesive exhibits good initial pressure-sensitive adhesive properties. In some embodiments, the uncured adhesive has an elastic shear modulus (G') less than or equal to 1MPa, 0.5MPa or 0.1MPa at 5°C. In some embodiments, the uncured adhesive has a G' less than 0.5MPa, 0.2MPa, 0.1MPa or 0.05MPa at 23°C. In some embodiments, the uncured adhesive has a G' less than 0.1MPa at a temperature within the range of 25°C to 70°C. G' can be reduced by reducing crosslinking (e.g., polyols) or adding tackifiers and / or plasticizers. G' can also be reduced by increasing the temperature at which the adhesive is applied.

[0081] In some embodiments, the cured adhesive has an elastic modulus E' greater than a comparative PSA adhesive at 23° C. In some embodiments, the cured adhesive has an elastic shear modulus (G') greater than 0.1 MPa, 0.5 MPa, 1 MPa, 2 MPa, 3 MPa, 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, 10 MPa, 11 MPa, 12 MPa, 13 MPa, or 14 MPa at 5° C. In some embodiments, the cured adhesive has an elastic shear modulus (G') greater than 0.05 MPa, 0.1 MPa, 0.5 MPa, 1 MPa, 2 MPa, 3 MPa, 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, or 10 MPa at 23° C. In some embodiments, the cured adhesive has a shear modulus of elasticity (G') at 70°C that is greater than 0.05 MPa, 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, or 0.5 MPa.

[0082] In some embodiments, the E' of the cured adhesive is at least 1E+05 (1×10 6 )Pa, 5E+05Pa, 1E+06Pa, 5E+06Pa, 1E+07Pa, 5E+07Pa, 1E+08Pa. In some embodiments, the E' of the cured adhesive is no greater than 1E+09Pa or 5E+08Pa, 1E+08Pa, 5E+07Pa, 1E+07Pa or 5E+06Pa.

[0083] In some embodiments, the cured adhesive has a Tan (δ) max that is less than the comparative adhesive. In some embodiments, the Tan (δ) max is less than 120° C., 110° C., 100° C., 90° C., or 80° C. In some embodiments, the Tan (δ) max is less than 70° C., 60° C., 50° C., 40° C., 30° C., or 20° C. In some embodiments, the Tan (δ) max is at least 10° C., 20° C., 30° C., 40° C., 50° C., 60° C., or 70° C.

[0084] In some embodiments, the cured adhesive composition has a gel content of at least 50 wt %, 60 wt %, 70 wt %, 80 wt % or 90 wt %. In some embodiments, the cured adhesive composition has a static shear greater than 10,000 minutes. In some embodiments, the cured adhesive composition has an impact strength of 0.4 joule to 1.8 joule, as measured by the tensile impact test method. In some embodiments, the cured adhesive composition has a push-out strength of 50 joule to 1040 joule, as measured by the push-out strength test method. In some embodiments, the cured adhesive composition has a dynamic shear of 0.5MPa to 7.32MPa, as measured by the dynamic shear test method.

[0085] Second floor

[0086] The adhesive article can be prepared by providing a curable adhesive composition on a second (eg core) layer comprising a polyvinyl acetal polymer. Such a second layer can be characterized as a carrier, (eg flexible) backing, or carrier layer.

[0087] Polyvinyl acetal polymers (also called resins) are known and are generally obtained by reacting polyvinyl alcohol with an aldehyde, as is known in the art.

[0088] The polyvinyl alcohol resin is not limited by the preparation method. For example, those polyvinyl alcohol resins prepared by saponifying polyvinyl butyrate or the like with alkali, acid, ammonia or the like can be used. The polyvinyl alcohol resin can be completely saponified or partially saponified. It is preferred to use those resins having a saponification degree of 80 mol% or more. The polyvinyl alcohol resin can be used alone or in combination of two or more.

[0089] The aldehydes used in the preparation of the polyvinyl acetal resin include formaldehyde (including paraformaldehyde), acetaldehyde (including paraldehyde), propionaldehyde, butyraldehyde, n-octanal, valeraldehyde, hexanal, heptaldehyde, 2-ethylhexanal, cyclohexylaldehyde, furfural, glyoxal, glutaraldehyde, benzaldehyde, 2-methylbenzaldehyde, 3-methylbenzaldehyde, 4-methylbenzaldehyde, p-hydroxybenzaldehyde, m-hydroxybenzaldehyde, phenylacetaldehyde, β-phenylpropionaldehyde, etc. These aldehydes can be used alone or in combination of two or more.

[0090] The polyvinyl acetal resin generally has a repeating unit represented by Chemical Formula 1.

[0091]

[0092] In Formula 1, n is the number of different types of aldehydes used in the acetalization; R 1 , R 2, ..., R n are independently a (e.g., C1-C7) alkyl residue or a hydrogen atom of the aldehyde used in the acetalization reaction;

[0093] k 1 , k 2 , ..., k n Independently contain R 1 , R 2 , ..., R n k is the ratio (molar ratio) of each acetal unit; l is the ratio (molar ratio) of the vinyl alcohol unit; and m is the ratio (molar ratio) of the vinyl acetate unit. 1 +k 2 +...+k n The sum of +l+m=1. In addition, k 1 , k 2 , ..., k n At least one of cannot be zero. When a single type of aldehyde is used in the preparation of the polyvinyl acetal resin, the single aldehyde may be 1 Indicates. 1 The number of repeating units of +l+m is sufficient to provide the desired molecular weight. In this embodiment, k 2 and k n Can be zero. Polyacetal resins are typically random copolymers. However, block copolymers and tapered block copolymers can provide similar benefits to random copolymers.

[0094] The content of polyvinyl acetal (e.g., butyral) is generally in the range of 65% to up to 90% by weight of the polyvinyl acetal (e.g., butyral) resin. In some embodiments, the content of polyvinyl acetal (e.g., butyral) is in the range of about 70% or 75% to up to 80% or 85% by weight. Therefore, the number of repeating units of "k1, k2, ..., kn" is selected accordingly.

[0095] The content of polyvinyl alcohol is generally in the range of about 10% to 30% by weight of the polyvinyl acetal (e.g., butyral) resin. In some embodiments, the content of polyvinyl alcohol is in the range of about 15% to 25% by weight. Therefore, "1" is selected accordingly.

[0096] The content of polyvinyl acetate can be zero or in the range of 1 wt % to 8 wt % of the polyvinyl acetal (e.g., butyral) resin. In some embodiments, the content of polyvinyl acetate is in the range of about 1 wt % to 5 wt %. Therefore, "m" is selected accordingly.

[0097] In some embodiments, the alkyl residue of the aldehyde contains 1 to 7 carbon atoms. In other embodiments, the alkyl residue of the aldehyde contains 3 to 7 carbon atoms, such as in butyraldehyde (R 1 =3), hexanal (R 1 =5), n-octanal (R 1 =7). Of these aldehydes, butyraldehyde, also known as butanal, is the most commonly used. Polyvinyl butyral ("PVB") resins are available under the trade name "Mowital TM " is commercially available from Kuraray and is marketed under the trade name "Butvar TM Commercially available from Solutia.

[0098] In some embodiments, the polyvinyl acetal (e.g., butyral) resin has a Tg ranging from about 60°C up to about 75°C or 80°C. In some embodiments, the Tg of the polyvinyl acetal (e.g., butyral) resin is at least 65°C or 70°C. When other aldehydes (such as n-octanal) are used in the preparation of the polyvinyl acetal resin, the Tg can be less than 65°C or 60°C. The Tg of the polyvinyl acetal resin is typically at least 35°C, 40°C, or 45°C. When the polyvinyl acetal resin has a Tg less than 60°C, a higher concentration of high Tg monomers can be employed in the film and (e.g., exemplified) composition compared to those utilizing polyvinyl butyral resins. When other aldehydes (such as acetaldehyde) are used in the preparation of the polyvinyl acetal resin, the Tg can be greater than 75°C or 80°C. When the polyvinyl acetal resin has a Tg greater than 70°C, higher concentrations of low Tg monomers can be used in films and (eg, exemplified) compositions than those using polyvinyl acetal butyral resins.

[0099] The polyvinyl acetal (e.g., PVB) resin typically has an average molecular weight (Mw) of at least 10,000 g / mol or 15,000 g / mol and no more than 150,000 g / mol or 100,000 g / mol. In some advantageous embodiments, the average molecular weight (Mw) of the polyacetal (e.g., PVB) resin is at least 20,000 g / mol, 25,000 g / mol, 30,000 g / mol, 35,000 g / mol and typically no more than 75,000 g / mol.

[0100] Those of ordinary skill in the art understand that another way to describe the molecular weight of a polymer is solution viscosity. Polyvinyl acetal (e.g., PVB) polymers are commercially available with a solution viscosity range of about 10 mPas to about 300 mPas in a 10 wt % polymer solution in ethanol and 5% water. In some embodiments, polyvinyl alcohol (e.g., butyral) polymers have a solution viscosity (viscosity of a 10 wt % polymer solution in ethanol and 5% water) of at least 40 MPas, 50 MPas, or 60 MPas and not more than 150 MPas, 140 MPas, 130 MPas, 120 MPas, or 100 MPas. A single polyvinyl (e.g., butyral) polymer can have this viscosity or a blend of two or more polyvinyl (e.g., butyral) polymers.

[0101] The second (e.g., core) layer comprises at least 50% by weight of a polyvinyl acetal (e.g., butyral) polymer, based on the total weight of the organic polymer of the second layer. In some embodiments, the amount of polyvinyl acetal (e.g., butyral) polymer may be at least 60%, 70%, 80%, 90%, or more by weight, based on the total weight of the organic polymer of the second layer. As demonstrated in the examples that follow, when the second layer has a higher concentration of polyvinyl acetal, the tape properties may be better.

[0102] The second polymer can be used to adjust the properties of the second layer. For example, the second polymer of the second layer can have a lower tensile strength and / or a higher elongation to improve the flexibility of the second layer. In some embodiments, the second polymer of the second layer has a tensile strength in the range of about 50 MPa to 100 MPa. In some embodiments, the second polymer of the second layer has an elongation at break in the range of about 250% to 500% (as measured according to DIN 53504).

[0103] In some embodiments, the second core layer comprises a blend of a polyvinyl acetal (e.g., butyral) polymer and a second thermoplastic polymer. In some embodiments, the second thermoplastic polymer is a thermoplastic polyurethane. The amount of the second (e.g., polyurethane) polymer is generally not greater than 50 wt %. In some embodiments, the amount of the second (e.g., polyurethane) polymer is generally not greater than 40 wt %, 30 wt %, 20 wt %, or 10 wt %, based on the total weight of the organic polymer of the second layer.

[0104] The second layer, particularly when formed by thermal coextrusion, is typically a continuous layer, i.e., over the length and width of the adhesive article. In some embodiments, the second layer is not a foam. In typical embodiments, the second layer does not contain an epoxy component.

[0105] Preparation method

[0106] The above-mentioned curable composition can be coated on the substrate using conventional coating techniques suitably modified according to a specific substrate. For example, these curable compositions can be applied to a variety of solid substrates by methods such as roller coating, flow coating, dip coating, spin coating, spray coating, scraping coating and die coating. Curable composition can also be coated by melt. These various coating methods allow composition to be placed on the substrate with variable thickness, thereby allowing composition to be used more widely. Coating thickness can vary according to the needs of specific application.

[0107] (e.g. tape) adhesive article comprises at least two layers, i.e. the first adhesive layer and the second backing or carrier layer containing polyvinyl acetal. In some embodiments, the second layer is arranged between the first layer and the third layer. The third layer may also include thermoplastic (e.g. heat-extrudable) adhesive composition. In some embodiments, the third layer is a curable adhesive identical to the first layer. Alternatively, the third layer may be different adhesive compositions.

[0108] The thickness of each layer is typically at least 5, 10, 15, 20, 25, 50, 75, 100, 125, 150, 175, or 200 microns, and is typically no greater than 1000 microns. When the second layer is formed by thermal coextrusion, the second layer is typically at least 100 microns. In some embodiments, the total thickness of the first and second layers is no greater than 2000, 1500, or 1000 microns.

[0109] In a preferred embodiment, the adhesive article is prepared by thermally coextruding the first layer and the second layer. Figure 1 It is a schematic diagram of an extrusion method suitable for preparing multilayer products. According to the method, initially the curable adhesive composition of the first layer is fed into the first extruder 10 (generally a single screw extruder), and the extruder softens the resin and grinds it into small particles suitable for extrusion. The curable adhesive composition of the first layer can be added to the extruder 10 in any convenient form (including pellets, ingots, bundles, strands and ropes). Then, the curable adhesive composition of the first layer and optional additives are fed to the second extruder 12 (for example, single screw or twin screw extruder) at a point before the kneading section of the extruder next to the extruder. Once combined, the curable adhesive composition and additives are fed to the kneading zone of the extruder 12, where they are fully mixed. Mixing conditions (for example, screw speed, screw length and temperature) are selected to achieve optimal mixing. When mixing is not required, for example, when there is no additive, the kneading step can be omitted. In addition, when the curable adhesive composition is already in the form suitable for extrusion, the first extrusion step can be omitted and the curable adhesive composition is directly added to the extruder 12.

[0110] After melt mixing, the extrudable polyvinyl acetal composition is metered into an extrusion die 14 (e.g., a contact die or a 15 drop die) through a certain length of a transmission pipeline 18 using a gear pump 16, which is used as a valve to control the die pressure. The temperature in the die 14 is preferably maintained at a temperature substantially the same as the temperature in the 20 transmission pipeline 18. The flow rate of the polyvinyl acetal composition through the extruder and the die outlet is maintained so that the polymer composition is processed by the die. The extrusion die can be a drop die, a contact die, a profile die, an annular die or a casting die, as known in the industry. More stringent tolerances are defined as the machine (or longitudinal) direction and the cross-web (or transverse) direction standard deviation (a / x) of density or thickness respectively relative to the average density or thickness. A / x is generally less than about 0.2, less than about 0.1, less than about 0.05 and even less than about 0.025.

[0111] The polyvinyl acetal composition may optionally be combined with a liner 20 dispensed from a feed roll 22. Suitable materials for the liner 20 include silicone release liners, polyester films (e.g., polyethylene terephthalate films), and polyolefin films (e.g., polyethylene films). The liner and polyvinyl acetal composition are then laminated together between a pair of rollers 24.

[0112] After lamination or after extrusion but before lamination, curable adhesive composition is optionally exposed to radiation from electron beam source 26 to crosslink curable adhesive. Other radiation sources (e.g., ion beam, heat and ultraviolet radiation) can also be used. Crosslinking can also be accomplished by using a chemical crosslinking method based on ionic interaction. Suitable thermal crosslinking agents include epoxides and amines. Preferably, concentration is low enough to avoid excessive crosslinking or gel formation before composition leaves die head. Crosslinking improves the cohesive strength of adhesive composition. After exposure, laminate is rolled onto take-up roll 28.

[0113] If desired, the smoothness of one or two surfaces in the curable adhesive composition surface can be increased by using a roller to press the foam against a cooling roller after the foam leaves the die head 14. Conventional micro-replication techniques can also be used, by contacting the adhesive with a patterned roller after the adhesive leaves the die head 14, extruding a pattern on one or two surfaces of the curable adhesive composition, the micro-replication techniques such as those disclosed in U.S. Patent No. 5,897,930 (Calhoun et al.), 5,650,215 (Mazurek et al.) and PCT Patent Publication No. WO 98 / 29516A (Calhoun et al.), all of which are incorporated herein by reference. According to the desired use of the foam, the replicated pattern can be selected from a wide range of geometric shapes and sizes. Substantially smooth surface improves micro-replication to higher precision and accuracy.

[0114] One or more layers of the curable adhesive composition are combined with at least one second polyvinyl acetal layer. Figure 1 As shown, the polyvinyl acetal composition is added to a second extruder 30 (e.g., a single screw extruder), where it is softened and melt mixed. The molten composition is then fed to a second extruder 32 (e.g., a single screw or twin screw extruder). After melt mixing, the extrudable polyvinyl acetal composition is metered into an extrusion die 14 (e.g., a contact die or a 15 drop die) through a certain length of a transmission conduit 18 using a gear pump 36, which is used as a valve to control the die pressure.

[0115] Additional layers (not shown) such as tie layers, primer layers, or barrier layers may also be included to enhance interlayer adhesion or reduce diffusion through the construction. In addition, interlayer adhesion of constructions having multiple layers of different compositions is achieved by blending a portion of the composition of the first layer into the composition of the second layer.

[0116] The first and second layers are usually Figure 1 In one embodiment (not shown), the second layer is coextruded between the first adhesive layer and the third adhesive layer. Alternatively, the first layer and the second layer can be extruded sequentially, i.e. at least one layer is cooled and solidified before extruding the other layer.

[0117] As is known in the art, extrusion processes generally produce orientation due to stretching in the machine direction. Orientation conditions include temperature, stretching direction, stretching rate, and stretching degree (ie, orientation ratio).

[0118] Objects and advantages of this disclosure are further illustrated by the following non-limiting examples, but the particular materials and amounts thereof recited in these examples, as well as other conditions and details, should not be construed to unduly limit this disclosure.

[0119] Example

[0120] Unless otherwise indicated or readily apparent from the context, all parts, percentages, ratios, etc. in the examples and the remainder of the specification are by weight.

[0121] Table 1. Materials used in the examples

[0122]

[0123]

[0124]

[0125] Test Method

[0126] Gel Permeation Chromatography (GPC) Test Method

[0127] The samples were prepared by weighing the sample and solvent in tetrahydrofuran (THF, stabilized with 250 ppm BHT); the target concentration was approximately 3 mg / mL. The sample solution was then filtered through a 0.45 micron PTFE syringe filter and analyzed by GPC under the following conditions:

[0128] Instrument: Agilent 1260LC

[0129] Column set: Waters Styragel HR 5E, 300mm×7.8mm ID

[0130] Column temperature: 40℃

[0131] Mobile phase: THF (stabilized with 250 ppm BHT), 1.0 mL / min

[0132] Injection volume: 30 μl Detector: Wyatt DAWN HELEOS-II 18-angle light scattering detector

[0133] Wyatt Optilab T-rEX Differential Refractive Index (DRI) Detector

[0134] The molecular weight results from GPC were determined in THF eluent using light scattering detection, and data collection and analysis were performed using an ASTRA 6 from Wyatt Technology Corporation. The differential refractive index increment (dn / dc) of each sample was experimentally determined in the mobile phase or eluent using the Total Recovery Approach. The results are averages from repeated injections and all dn / dc values ​​are in mL / g. The experimental dn / dc values ​​are used for molecular weight calculations.

[0135] M n =Number average molecular weight

[0136] M w =Weight average molecular weight

[0137]

[0138] Samples for peel adhesion and static shear adhesion tests were prepared by laminating UV-curable pressure-sensitive adhesive tapes to 0.13 mm thick anodized aluminum foil using a handheld rubber roller, unless otherwise noted. 4 J / cm2 (about 1.1 W / cm2) from a 365 nm AC7300 LED light source (Excelitas Technologies, Waltham, MA, USA) of Waltham, MA) was used to irradiate the test tapes. Total UVA energy was measured using a POWER PUCK II radiometer (purchased from EIT Co., Ltd., Sterling, Virginia) equipped with a high-power sensing head. Stainless steel substrates were cleaned with methyl ethyl ketone, 1:1 isopropyl alcohol / water, acetone, and then dried with KIMWIPE (Kimberly-Clark, Irving, TX) unless otherwise noted.

[0139] Peel Adhesion

[0140] A 12.5 mm wide adhesive strip was applied to anodized aluminum foil, UV activated, and then laminated to a 1.6 mm thick stainless steel plate using a 2.0 kg rubber roller to obtain a bonded product. The product was allowed to stay for 72 hours under CTH conditions. According to test method ASTM Designation D3330 / D330M-04, a 90° angle peel test was performed using an MTS Sintech 500 / S at a peel rate of 30.5 cm / min, with data collected and averaged within 10 seconds. Uncured peel adhesion samples were prepared as described above, except that the UV exposure step was skipped.

[0141] Static Shear Adhesion

[0142] Static shear adhesion was determined according to the test method of ASTM D3654 / D3654M-06. A 25.4 mm x 12.7 mm UV-cured adhesive strip was applied to an anodized aluminum foil, UV-activated, and then laminated to a 1.6 mm thick stainless steel plate using a 2.0 kg rubber roller to obtain a bonded article. The article was allowed to rest for 24 hours, and then a 0.5 kg weight was attached to the assembly by extending the remaining length of the aluminum foil beyond the bonding area and maintained at 70°C. The time was measured when the adhesive sample could not hold the weight. If the sample did not fail quickly, stop at 10,000 minutes.

[0143] Push Strength

[0144] A sample of the test tape having a siliconized PET liner on both surfaces was cut into a circular ring geometry of 3.11 cm outer diameter and 2.61 cm inner diameter (2.5 mm bond width). One liner was removed, exposing the adhesive surface, and the tape was adhered to the surface of a square polycarbonate test frame (4.07 cm x 4.07 cm x 0.3 cm) with a circular hole (2.4 cm diameter) cut in the middle; wherein the tape was placed in the center of the hole. The second liner was removed from the test tape, and the tape was irradiated with 4 J / cm2 of 365 nm UV-LED light. A POWERPUCK II radiometer (available from EIT Inc., Sterling, VA) equipped with a high power sensing head was used to measure the total UVA energy. Immediately after irradiation, a polycarbonate disk (3.3 cm diameter × 0.3 cm thick) was placed in the center of the test strip and attached to the polycarbonate frame surface using a 10 kg weight, which was placed on the bonded polycarbonate disk, strip, polycarbonate frame product for 10 seconds. The weight was removed and the test fixture was left at CTH for 24 hours. The disk was then separated from the frame that remained stationary using an MTS Sintech 500 / S (MTS, Eden Prairie, MN), a probe was used to pass through the hole of the frame at a rate of 10 mm / min, and the total force was recorded and three repetitions were completed for each sample.

[0145] Tensile shock

[0146] The samples were prepared as described in the push-out strength method, except that the frame and disk base were made of stainless steel instead of polycarbonate. The samples were tested using an Instron CEAST 9340 drop tower with a mass of 3 kg at a drop height of 300 mm, where the impact passed through a hole in the fixed frame, causing the disk to separate from the frame. The total energy and failure mode were recorded and three replicates were completed for each sample.

[0147] Dynamic shear

[0148] A stainless steel substrate (25.4 mm x 76.2 mm x 1.6 mm) was cleaned with methyl ethyl ketone, 1:1 isopropyl alcohol / water, acetone, and then dried with KIMWIPE (Kimberly Clark, Irving, Texas). A 1 inch by 1 inch tape sample with a PET liner on one surface was firmly bonded to the stainless steel substrate opposite the PET liner using finger pressure. The PET liner was then removed. The test tape was irradiated with 4 J / cm2 of 365 nm UV-LED light. A POWER PUCK II radiometer (purchased from EIT, Inc., Sterling, Virginia) equipped with a high power sensing head was used to determine the total UVA energy. A second clean stainless steel substrate was bonded to the UV-cured tape. The sample was mechanically rolled at 305 mm / min with a 6.8 kg roller to ensure proper adhesion. The sample was allowed to stay under CTH conditions for 24 hours. The substrate was attached to two separate clamp hooks in an MTS Insight 30 (MTS, Eden Prairie, MN) and separated at a rate of 12.7 mm / min.

[0149] Gel content

[0150] All samples were cut using a 2.54 cm diameter die, weighed, and placed in pre-weighed metal pouches. The pouches were immersed in THF for three days. The pouches were removed from the solvent and dried in a solvent oven (Blue M, Model DC-246AG-HP) at 120°C for 4 hours. The samples were then weighed again and the weight change was recorded.

[0151] Tensile dynamic mechanical analysis

[0152] The samples were cured and laminated to a thickness of 800 μm, then cut into 6.35 mm strips and placed on a TA Instruments Q800 DMA. The strips were oscillated at 1 Hz and 2% strain using a temperature ramp from -60°C to 150°C with a heating rate of 2°C / min.

[0153] Shear rheology

[0154] A Discovery Hybrid parallel plate rheometer (TA Instruments) was used to measure shear rheology to characterize the physical properties of each sample as a function of temperature. Rheological samples were prepared by punching out segments of the PSA with an 8 mm circular die, removing them from the release liner so that their centers were located between the 8 mm diameter parallel plates of the rheometer, and compressing until the edges of the sample were unified with the edges of the top and bottom plates. The oven door around the parallel plates and the axis of the rheometer was closed, and the temperature was equilibrated at 20°C and held for 1 minute. The temperature was then raised from 20°C to 125°C or 130°C at 3°C / min while oscillating the parallel plates at an angular frequency of 1 Hz and a constant strain of 5%.

[0155] Preparation Example

[0156] Synthesis of Preparation Example 1 (PE1)

[0157] Methyl methacrylate (11 grams) was combined with butyl acrylate (39 grams) in a 200 mL glass jar equipped with a stir bar. Ethyl acetate (100 grams), IOTG (0.075 grams), and VAZO 67 (0.05 grams) were then added and the solution was purged by bubbling nitrogen through the solution for a period of 5 minutes before placing a lid on the jar. The jar was placed in a water bath set at 70° C. on a stir plate for a period of 24 hours. The solvent and residual monomers were removed by a vacuum oven set at 40° C. at a pressure of -30 inches Hg.

[0158] Example

[0159] Examples CE-3 and EX-1 to EX-4 in Table 2 were prepared by combining the listed materials in a jar and tumbling for 24 hours before coating. Tapes were prepared by pouring the solution onto PET1 and then passing it under a notched bar coater set with a gap of 24 mils (610 μm). The tapes were then placed in a ventilated oven (Blue M, Model DC-246AG-HP) set at 70° C. for a period of 5 minutes. Two layers of each tape were laminated together to prepare thicker samples.

[0160] Table 2. Composition of UV-activated tapes used to study the effect of polyol concentration

[0161]

[0162] Examples EX-5 to EX-11 in Table 3 were prepared using a batch twin-screw extruder with the following settings:

[0163] Extruder and melt unit component temperature: 250°F (121°C)

[0164] Hose and die temperature: 280℉(138℃)

[0165] Screw speed: 150rpm

[0166] Upon exiting the die, the melt was coated onto a PET1 liner. The sample was then wound into a roll. The extruded sample was a transfer tape 80 μm - 145 μm thick. These tapes were then laminated to twice the thickness, between 160 μm - 290 μm.

[0167] Table 3. Composition of UV-activated tapes prepared using a batch twin-screw extruder

[0168] example Final thickness(mm) LA2330 LA2140 828 2200 6976 ENR50 4454 Q3620 IRG 1010 EX-5 200 39.0 0.0 29.3 29.3 2.0* 0.0 0.0 0.0 0.5 EX-6 250 39.0 0.0 29.3 29.3 2.0 0.0 0.0 0.0 0.5 EX-7 180 0.0 39.0 29.3 29.3 2.0 0.0 0.0 0.0 0.5 EX-8 200 29.3 0.0 29.3 29.3 2.0 0.0 9.8 0.0 0.5 EX-9 160 19.5 0.0 29.3 29.3 2.0 0.0 19.5 0.0 0.5 EX-10 290 29.3 0.0 29.3 29.3 2.0 9.8 0.0 0.0 0.5 EX-11 250 29.3 0.0 29.3 29.3 2.0 0.0 0.0 9.8 0.5

[0169] *Use PI 2074 / ITX (1:1) instead of CPI 6976

[0170] Examples EX-12 through EX-19 in Table 4 were prepared using a 12-zone continuous hot melt extruder with an average temperature of 250°F (121°C) and a screw speed of 500 rpm.

[0171] Upon exiting the die, the melt was coated onto the PET1 liner and then laminated with the PET2 liner. The sample was then wound into a roll.

[0172] Table 4. Composition of UV-activated tapes prepared using a continuous twin-screw extruder

[0173] example Final thickness(mm) LA2330 828 2200 6976 1001 IRG 1010 Q3620 DUALITE EX-12 200 29.1 29.1 29.1 1.9 1.0 9.7 0.0 EX-13 250 38.8 29.1 29.1 1.9 1.0 0.0 0.0 EX-14 180 48.5 24.3 24.3 1.9 1.0 0.0 0.0 EX-15 200 34.0 29.1 29.1 1.9 1.0 4.9 0.0 EX-16 160 38.5 28.8 28.8 1.9 1.0 0.0 1.0 EX-17 290 48.1 24.0 24.0 1.9 1.0 0.0 1.0 EX-18 250 33.7 28.8 28.8 1.9 1.0 4.8 1.0 EX-19 210 50 22 8 2 20 1.0

[0174] Examples EX-20 and CE-4 in Table 5 were prepared by combining the listed materials in a jar and tumbling for 24 hours before coating. Tapes were prepared by pouring the solution onto PET1 and then passing it under a notched bar coater set with a gap of 24 mils (610 μm). The tapes were then placed in a ventilated oven (Blue M, Model DC-246AG-HP) set at 70° C. for a period of 5 minutes. Two layers of each tape were laminated together to prepare thicker samples.

[0175] Table 5. Preparation of tapes for comparison of random acrylic copolymers and block acrylic copolymers

[0176] example Final thickness(mm) LA2330 PE1 828 4013F ITX 250 Q3620 EX-20 200 34.0 0.0 29.1 29.1 1.0 1.9 4.9 CE-4 250 0.0 34.0 29.1 29.1 1.0 1.9 4.9

[0177] Table 6. Adhesion properties of UV activated tapes

[0178]

[0179]

[0180] Table 7. Rheological data of selected UV activated tapes

[0181] example Cured E'(pa) at 23℃ Cured Tan(δ)max(℃) CE-3 4.50E+08 128 EX-1 4.75E+08 81 EX-2 3.37E+08 57 EX-3 8.32E+07 40 EX-4 6.17E+06 21 EX-12 3.70E+06 14 EX-13 2.93E+06 19 EX-14 2.60E+06 30 EX-15 3.67E+06 17

[0182] The epoxidized natural rubber ENR50 solution was prepared by grinding ENR50 for 4 minutes with an extruder at a screw speed of 400 rpm and then dissolving in toluene to obtain a 35 wt% solution. The ENR50 solution was combined with 828, D1119 and a curing catalyst as shown in Table 8. The material was coated onto the silicone surface of a PET1 liner using a notched bar with a wet gap of 12 mils and dried at 74°C (165°F) for a period of 9 minutes. After drying, the silicone surface of the PET1 liner was laminated to prepare an adhesive transfer tape.

[0183] Table 8. Curable adhesive tapes with epoxidized natural rubber, styrene block copolymers, and epoxy resins

[0184] example ENR50 828 D1119 OMICURE 6976 Uncured peel (N / cm) Cured peel (N / cm) EX-21 50 8.75 0.0 4.3 0.0 1.67 40.3 EX-22 107 50 0.0 0.0 0.5 4.72 29.7 EX-23 35.71 50 37.5 7 0.0 0.04 20.0 EX-24 71.43 50 25 7 0.0 2.91 33.7 EX-25 107.14 50 12.5 7 0.0 5.28 36.4

[0185] Table 9. Core composition of multilayer tapes

[0186]

[0187] Table 10. Adhesive compositions of multilayer tapes

[0188]

[0189] The material of Table 9 was prepared using a 10-zone continuous hot melt extruder with an average temperature of 250°F (121°C) and a screw speed of 500rpm. The material of Table 10 was compounded in a separate continuous hot melt extruder set at 360°F and a screw speed of 200rpm. The output from the two extruders was combined into a 3-layer die set at 200°F. Upon leaving the die, the melt was coated on the PET1 liner and then laminated with the PET2 liner. The sample was then wound into a roll. The line speed was adjusted as needed to achieve the desired total construction thickness of 600 μm, with each individual layer being 200 μm.

[0190] The resulting strips were tested using the test method described previously. The test results are as follows:

[0191] Table 11. Multilayer tape test results

[0192]

[0193] The adhesive compositions of Examples 1 to 24 can also be disposed on the layer comprising polyvinyl acetal in the same manner (eg, by thermal coextrusion).

Claims

1. An article comprising a first layer, the first layer comprising a curable adhesive composition, wherein the curable adhesive composition comprises: 20 to 60 wt % of an acrylic block copolymer; 5 to 60 wt % epoxy resin; and 1 to 60 wt % of a polyol; and The first layer is disposed on a second layer comprising a polyvinyl acetal polymer.

2. The article of claim 1, wherein the second layer comprises at least 50%, 60%, 70%, 80% or 90% by weight of the polyvinyl acetal polymer.

3. The article of claims 1 to 2, wherein the first and second layers independently have a thickness in the range of 5 microns to 1000 microns.

4. The article of claims 1 to 3, wherein the second layer is disposed between the first layer and the third layer, and the third layer comprises a thermoplastic adhesive composition.

5. The article of claims 1 to 4, wherein the third layer is the same curable adhesive as the first layer.

6. The article of claims 1 to 5, wherein the acrylic block copolymer comprises 7 to 51 wt% hard blocks and 49 to 93 wt% soft blocks.

7. The article of claim 6, wherein the hard block comprises polymethyl methacrylate.

8. The article of claim 6-7, wherein the soft block comprises polybutyl acrylate.

9. The article of claim 1 to 8, wherein the acrylic block copolymer has a number average molecular weight of 48 kD to 102 kD, optionally 65 kD to 101 kD, or optionally 75 kD to 100 kD.

10. The article of claim 1 to 9, wherein the epoxy resin has an epoxy equivalent weight of 150 to 250.

11. The article of claim 1 to 10, wherein the epoxy resin comprises a first epoxy resin and a second epoxy resin combined in a ratio of 0.5:1.5, optionally 0.75:1.25, or optionally 1:

1. 12 . The curable composition of claim 11 , wherein the second epoxy resin has an epoxy equivalent weight of about 500 to about 600.

13. The curable composition of claims 1 to 12, wherein the epoxy resin comprises a bisphenol A derived epoxy resin.

14. The curable composition of claims 1 to 13, wherein the polyol has a molecular weight of 500 g / mol to 14,000 g / mol.

15. The curable composition of claims 1 to 14, wherein the polyol comprises a polyether polyol, a polyester polyol, and combinations thereof.

16. The curable composition according to claims 1 to 15, further comprising a curing agent selected from the group consisting of an amine curing agent, a photoinitiator, and a combination thereof.

17. The article of claims 1 to 16, wherein the adhesive composition is cured and has an impact strength of 0.4 to 1.8 Joules as measured by the Tensile Impact Test Method.

18. The article of claims 1 to 17, wherein the adhesive composition is cured and has a push-out strength of 50 Joules to 1040 Joules as measured by the Push-out Strength Test Method.

19. The article of claims 1 to 18, wherein the adhesive composition is cured and has a dynamic shear of 0.5 MPa to 7.32 MPa as measured by the Dynamic Shear Test Method.

20. An article comprising a first layer, the first layer comprising a curable adhesive composition, wherein the curable adhesive composition comprises: Thermoplastic polymers; and Epoxy resin; and The first layer is disposed on a second layer comprising at least 50 weight percent polyvinyl acetal polymer.

21. A method of preparing an article, the method comprising: The first and second layers according to claims 1 to 19 are hot extruded.

22. A curable adhesive composition, wherein the curable adhesive composition comprises: 20 to 60 wt % of an acrylic block copolymer; 5 to 60 wt % epoxy resin; and 1 to 60 wt % of a polyol; and Optional additives.

23. The curable adhesive of claim 22, further characterized by claims 2 to 19.

Citation Information

Patent Citations

  • Adhesive tapes

    US10774245B2

  • Complex salt photoinitiator

    US4173476A

  • Sensitized aromatic iodonium or aromatic sulfonium salt photoinitiator systems

    US4250053A

  • Photocopolymerizable compositions based on epoxy and hydroxyl-containing organic materials

    US4256828A

  • Epoxy resin curing agent, process and composition

    US4503211A